Why Are Child and Youth Welfare Support Services Initiated? A First-Time Analysis of Administrative Data on Child and Youth Welfare Services in Austria - Katja Haider; Stefan Kaltschik; Manuela Amon; Christoph Pieh (MDPI AG, 2023)
Even if numerous children and young people are looked after by child and youth welfare, there are only a few scientific studies on the reasons for this support. The aim of this retrospective descriptive study was to examine the reasons why child and youth welfare was initiated. Therefore, administrative data, collected by the Lower Austrian Child and Youth Welfare Service, from the year 2021 will be presented. On the one hand, the frequencies of the different justifications provided by the social workers and, on the other hand, whether these are primarily based on problems of the parents/caregivers or the children are reported. In 2021, a total of 7760 clarifications of child welfare endangerments were initiated. The descriptive statistical analyses showed that the most frequent concerns were parental overload (49%), behavioral issues (10%), and difficult economic conditions (9%). Although a classification according to the caregiver or child level cannot always be clearly distinguished, there is a trend that in many cases (84% to 99% depending on the type of support) the problems lie at the caregiver level. Further studies are necessary so that the care of such vulnerable groups of people will be better supported by scientific findings.